NATURA 2000 IN ROMANIA - A DECADE OF GOVERNANCE CHALLENGES - Steluta Manolache; Cristiana Maria Ciocanea; Laurentiu Rozylowicz; Andreea Nita (European Journal of Geography)
Prior to Romania’s joining the European Union in 2007, the Romanian government assumed the responsibility to fully implement Community legislation in the field of nature conservation. This led to a rapid increase of protected surface areas (from 7% in 2005 to 20% in 2009) and a significant overlapping of EU and national protected areas. Due to a lack of resources, the governance of protected area transformed from state management exclusitory to a participatory one. Currently, the Romanian government is still a key actor in conservation and governance of protected area, organizing the decision-making process but delegating the responsibility for the implementation of the conservation policies to other organizations (e.g., local public bodies, enterprises, NGOs). We outline the changes in protected areas governance and highlight the emerging key non-governmental participants. Furthermore, we compare Romania’s case to other governance models and discuss opportunities for a more decentralized system. A transparent decision-making approach is required for a better interconnection between all the institutions involved in the administration and also for improving governance of Natura 2000 protected areas in Romania.